Analisis Faktor-Faktor yang Memengaruhi Ekspor Minyak Kelapa Sawit (CPO dan Turunannya) Indonesia Tahun 1990-2022 - Putri, Nabila Aurelliza Candrika; Yuliana, Rita (Politeknik Statistika STIS, 2024)
International trade plays an important role in economic development, including for Indonesia, which is the world's largest producer and exporter of palm oil in 2021. However, in recent years, palm oil exports have fluctuated, worsening Indonesia's non-oil and gas trade balance. However, domestic palm oil stocks are still large, providing an opportunity to maximize exports amid rising international prices. This study aims to analyze the development of palm oil exports and the factors that influence them in the long and short term from 1990 to 2022 using the Autoregressive Distributed Lag (ARDL) method. Palm oil exports have an increasing trend. In the long term, production, international prices, domestic investment, and foreign investment affect exports. Meanwhile, export lag, real exchange rate, production, real interest rates, and PMDN affect exports in the short term. Simplification of export regulations and investment management can be a concern for the government to increase Indonesian palm oil exports.